A PERSPECTIVE ON AGRICULTURAL LABOR PRODUCTIVITY AND GREENHOUSE GAS EMISSIONS IN CONTEXT OF THE COMMON AGRICULTURAL POLICY EXIGENCIES - Constantin, Marius; Radulescu, Iuliana Denisa; Andrei, Jean Vasile; Chivu, Luminita; Erokhin, Vasilii; Gao, Tianming (Economics of Agriculture, 2021)
European agriculture is the result and experiences of a numerous and md determinant reforms during last period of time. Labor productivity and green gas emissions represents two major turning points in analyzing the Common Agricultural Policy evolution. The main aim of this research is to make a synoptic analysis of the agriculture evolution in context of the new Common Agricultural Policy paradigm transformation from the perspective of sectorial structural changes determined by the new environmental exigencies and labor productivity.